2018
DOI: 10.1155/2018/4528704
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dietary Patterns and Precocious Puberty in Children: A Population-Based Study

Abstract: Objective The aim of the present study was to investigate the association between dietary patterns and precocious puberty among Shanghai children. Methods A cross-sectional study was conducted among Shanghai children by multistage stratified cluster random sampling in June 2014. Diet was assessed using a simplified food frequency questionnaire (FFQ). Height, weight, and Tanner stages of breast development, pubic hair growth, and testicular volume were carefully measured. Exploratory factor analysis was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 42 publications
1
34
1
2
Order By: Relevance
“…Knowledge on specific type of dietary patterns might influence age at menarche among Chinese girls is lacking. A recent cross-sectional study of children in Shanghai found that unhealthy diet pattern, characterized by high intakes of dessert/snacks, soft drinks, and fried food, was positively associated with precocious puberty in girls [20]. However, this study was cross-sectional, and did not adjust for other potential confounding factors, such as energy intake.…”
Section: Introductionmentioning
confidence: 81%
“…Knowledge on specific type of dietary patterns might influence age at menarche among Chinese girls is lacking. A recent cross-sectional study of children in Shanghai found that unhealthy diet pattern, characterized by high intakes of dessert/snacks, soft drinks, and fried food, was positively associated with precocious puberty in girls [20]. However, this study was cross-sectional, and did not adjust for other potential confounding factors, such as energy intake.…”
Section: Introductionmentioning
confidence: 81%
“…The "traditional diet" was not associated with ESM in children. Similarly, Chen et al [11] found no association between precocious puberty and "traditional diet" included white meat, seafood, vegetables, fruits, and dairy products. Our "traditional diet" pattern included a high intake of animal protein which has been found not associated with early menarche [39,40].…”
Section: Discussionmentioning
confidence: 97%
“…Notably, no signi cant association was observed between the "whole grain and fat" pattern and ESM [10]. These contrasting ndings may be attributed to differences between Eastern and Western DPs, differing study designs, and the variety of statistical methods used to obtain DPs, such as principle component analysis and factor analysis [10][11][12][13]. Moreover, none of the aforementioned studies applied reduced-rank regression (RRR) to extract DPs in relation to ESM.…”
mentioning
confidence: 99%
See 2 more Smart Citations